PENGARUH CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN DI INDONESIA - Hasanah, Ni'matul; Syam, Dhaniel; Jati, Ahmad Waluya (Universitas Muhammadiyah Malang)
This study aims to examine the effect of Corporate Governance Effect on Sustainability Report Disclosure Report. This sample of 30 companies listed on the Indonesia Stock Exchange (IDX) in 2013 with purposive sampling technique. The data was analized with multiple linear regression. The result of the research stated that the average of attendance level of board of commissioners, board of directors and audit committee in the meeting did not affect the disclosure of sustainability report. Keyword: Corporate Governance, Sustainability Report